Global Nuclear Developments - Ikonomou, Pantelis F. author. aut Link
XXI, 183 p. 4 illus., 2 illus. in color.
Keywords: Written by a former International Atomic Energy Agency (IAEA) nuclear inspector and nuclear security expert, this book provides a comprehensive and authentic overview of current global nuclear developments. The author provides detailed insights into current and past nuclear crises and reveals the technical capabilities, political strategies and motives of nuclear weapon owners. By analyzing the nuclear programs and strategies of various countries, including the USA, Russia, China, Great Britain and France, this book highlights the existing global nuclear threat and the risks it entails for humanity. It also describes the current blockades and suggests possible ways out. Given its scope, the book will appeal to scholars and policymakers interested in gaining new insights into sensitive or complex nuclear programs in various countries.